Efektivitas Latihan Strokes dengan Shadow dan Audio Visual terhadap Akurasi Dropshot Bulutangkis - RD. Devy Citra Pratiwi (Institut Teknologi Bandung, 2022)
Dropshot is one of the trick techniques in badminton, a good dropshot direction falls behind the double line. In badminton athletes aged 11-12 years the dropshot accuracy is still not good, the shuttlecock often falls far from the net or behind the short serve line. Based on these observations, it is necessary to have a form of training to improve dropshot accuracy. This research was conducted with the aim of knowing the effectiveness of strokes training with shadows and audio visual on dropshot accuracy. This study uses a quasi-experimental method, the design used in this study is the Two Groups Pretest-Posttest Design. The research subjects consisted of 14 badminton athletes aged 11-12 years (7 athletes in group A and 7 athletes in group B). With the sampling technique using purposive sampling, data analysis in this study used the t test. The results of this study showed that group A had a significant effect of strokes training with shadow on dropshot accuracy, with an increase in dropshot accuracy of 23.09% compared to the results in group B strokes training with audio visual, the magnitude of the increase in dropshot accuracy was obtained by 16.77%. So it can be concluded that strokes training with shadow has a better effect on badminton dropshot accuracy for athletes aged 11-12 years. Keywords: Strokes practice, Shadow, Audio Visual, Dropshot Accuracy, Badminton